A educação ambiental na formação do pedagogo: a dimensão ambiental no curso de Licenciatura Plena de Pedagogia da UFPB João Pessoa - Lopes, Theóffillo da Silva (2012)
Understanding the environmental issues and social crisis that has all the postmodern society is something latent, we observed that caring is an education that is perceived within this context. An education is not only transmitted within the school environment, but beyond it. That is formed and transformed through the proper training of educators. To this end, this research sought to investigate the environmental inserted in the Faculty of Education UFPB Campus I. For this, we used a qualitative methodology approach document/literature for analysis of the Political Pedagogical Course, as well as the menus and programs of the same disciplines. Was also developed semi-structured questionnaires with teachers and students of the course, so in order to identify how the environmental dimension has been inserted in the educational training of educators. As a result we obtained evidence that the environmental dimension is inserted into the vanishingly PPP, menus and programs of the disciplines, and that even being already known and recognized by the faculty interdisciplinary and cross to the students, this design still is not present, revealing the need for further discussion and reflection on the scale.